The Effect of Training and Its Impact on the Performance of Agricultural Investors in the Nias District - Adventina Dachi; Prihatin Lumbanraja; Pardamean Daulay (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research investigates the influence of training initiatives on the performance of agricultural investors in the Nias District. With the agricultural sector playing a crucial role in the district's economy, enhancing investor performance becomes essential for sustainable growth. Initial findings suggest a positive correlation between training participation and investor performance. Training programs are shown to equip agricultural investors with valuable skills, knowledge, and techniques, enabling them to make informed decisions, optimize resource utilization, and implement best practices. Additionally, the study identifies various factors influencing the effectiveness of training, including program content, delivery methods, and ongoing support. In conclusion, this study emphasizes the significance of training programs in enhancing the performance of agricultural investors within the Nias District.